Implementation of the QCDMSE Strategy in the Community Empowerment Program to Utilize the Sulawesi Masked Owls as a Natural Predator for Rodents - Abdil Halimis Stani; Cut Desy Ariani; Didi Supriyadi; M. Isyaraqi Gazian (Prospect: Jurnal Pemberdayaan Masyarakat, 2023)
Rodent pest is known for its detrimental impact on agriculture where it is responsible for for more than 10% of crop loss across worldwide. Although a number of conventional rodent-control methods such as electric current, fumigation, trapping and rodenticide are applied, however there are growing concerns related to their effectiveness and safety concerns. Joint Operating Body Pertamina – Medco E&P Tomori Sulawesi (JOB Tomori) initiated community development program to address this issue by utilizing Sulawesi Masked Owl as agricultural rodent control. Starting from 2017, at approximately 84 artificial nest boxes and 175 perch pillars were installed in paddy fields located in 3 subdistrict in Banggai, Central Sulawesi. Here we present a novel approach of using QCDSME strategy in the context of the community empowerement program. The advantages, limitations, lesson learned and further recommendation of the QCDSME approach are also discussed in this paper.